DATA MINING UNTUK PENEMPATAN BARANG BERDASARKAN FREKUENSI PERMINTAAN DI PT LAUTAN LESTARI SHIPYARD - Mendrofa, Nober Six Salvanius; Sitohang, Sunarsan (Computer Science and Industrial Engineering, 2022)
Good arrangement of goods in the warehouse is one of the important things in supporting the activities of a company. At PT Lautan Lestari Shipyard, the placement of goods in its warehouse is still relatively irregular and looks messy, this is because the placement is not based on the frequency of the number of goods coming out. This study aims to apply data mining in the preparation of the layout of goods by utilizing the archive of goods expenditure data available at the company by using the algorithm method k-means clustering. From this research, 5 data clusters were found to be the most optimal with a Davies Bouldin Index (DBI) value of 0.288. This research is expected to help make it easier for companies to arrange the goods in the warehouse.